The Use of the T-Ex Approach in Indonesian EFL Essay Writing: Feedbacks and Knowledge Exploration - Gidion Maru, Mister; Matheos Ratu, Donal; Marhaenny Dukut, Ekawati (International Journal of Engineering and Technology, 2018)
This research paper is aimed at sharing the knowledge exploration occurring in an EFL classroom which becomes the impact of giving corrective feedbacks within the implementation of the T-Ex Approach in teaching essay writing In Indonesia EFL Class. T-Ex approach, which is originally called Jeremiad approach, suggests three aspects namely text explanation which prescribes the identification and presentation of a certain given topic or issue, text examination that underlines the presence of possibly related knowledge toward the topic, and text expectation that proposes the reflection and application of the knowledge-found into the ongoing context. As a qualitative research, this study involves students as the respondents to be interviewed after being taught using the approach and given feedbacks. The data are coded by use of grounded theory. The results reveal that the written corrective feedbacks in the implementation of the T-ex approach has led the students to explore their heuristic intuition in dealing with the challenge of source exploration, challenge of linguistic knowledge, the focus on the comprehensiveness of the topic, and the possibility of interdisciplinary studies. The essay writing itself reflects a process of searching and thinking as well as the sharing of knowledge, language and values.Â Â